Amendment of Rostellotaenia Freze, 1963 (Cestoda: Proteocephalidae) from African monitors (Varanus spp.) and a redescription of its type-species, R. nilotica (Beddard, 1913) - Scholz, Tomáš; de Chambrier, Alain (Systematic parasitology, 2019)
Based on morphological evaluation of type-specimens and new material collected in three species of monitor lizards (Squamata: Varanidae), the diagnosis of the monotypic Rostellotaenia Freze, 1963 (Proteocephalidae: 'Acanthotaeniinae') is amended. The genus differs from Acanthotaenia von Linstow, 1903, with which it was previously synonymised, by the shape of the scolex with a wide, dome-shaped rostellum, the posterior extent of the uterus, which does not overpass the ovarian isthmus posteriorly, well-developed retractor muscles connecting the rostellum with the neck region, absence of a well-developed, ring-like vaginal sphincter, shorter and wider proglottides, and geographical distribution (Ethiopian region only). The type- and only species, R. nilotica (Beddard, 1913), is redescribed and two new definitive hosts, Varanus albigularis Daudin and V. exanthematicus (Bosc), are reported. Host specificity of R. nilotica, which exhibits remarkable morphological variability, is stenoxenous, i.e. it occurs in several congeneric species of African monitor lizards, unlike species of Acanthotaenia, which are strictly specific (oioxenous).
Keywords: Cestoda; Lizards; Phylogeny; druhová specificita; ještěři; Animals; Species Specificity; zvířata; fylogeneze